2018
DOI: 10.1007/s00053-018-0250-z
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequenzablation (Rafaelo®-Prozedur) zur Therapie von prolabierenden Hämorrhoiden III°

Abstract: Hintergrund und FragestellungDas Hämorrhoidalleiden ist eine häufige proktologische Erkrankung und kommt in unterschiedlichen Ausprägungen mit den typischen Symptomen Juckreiz, Schmerz, Blutung und Nässen vor. In höheren Stadien (III-IV°) wird eine operative Therapie bevorzugt, während in den weniger fortgeschrittenen Stadien (I-II°) stuhlregulative Strategien sowie lokale ambulante Therapien wie Verödung und Gummibandligaturen mit Erfolg zur Anwendung kommen.In Deutschland werden im Falle einer operativen The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
1
6
0
1
Order By: Relevance
“…Radiofrequency hemorrhoidal treatment, excepting Ligasure (Medtronic, Dublin, Ireland) and harmonic scalpels that are nonconservative surgical techniques, has been poorly studied; therefore, this study started from limited data. At the end of the study in September 2021, the literature review of published studies using PubMed Central (keywords: "radiofrequency and hemorrhoids, " "RFITT, " "Rafaelo procedure, " "radiofrequency thermocoagulation" except Ligasure) showed publications from only 8 different centers (1 in India [26], Czech [27], Germany [28], and Russia [29] and 2 in the United Kingdom [30,31] and France [20,32]). There are no publications comparing RFT following Rafaelo procedure with other surgical techniques, but one with DGHAL and RFT combined [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiofrequency hemorrhoidal treatment, excepting Ligasure (Medtronic, Dublin, Ireland) and harmonic scalpels that are nonconservative surgical techniques, has been poorly studied; therefore, this study started from limited data. At the end of the study in September 2021, the literature review of published studies using PubMed Central (keywords: "radiofrequency and hemorrhoids, " "RFITT, " "Rafaelo procedure, " "radiofrequency thermocoagulation" except Ligasure) showed publications from only 8 different centers (1 in India [26], Czech [27], Germany [28], and Russia [29] and 2 in the United Kingdom [30,31] and France [20,32]). There are no publications comparing RFT following Rafaelo procedure with other surgical techniques, but one with DGHAL and RFT combined [29].…”
Section: Discussionmentioning
confidence: 99%
“…The Rafaelo technique used in this study is radically different by introducing an electrode directly into the internal hemorrhoidal pack. Duben et al [34] described its pilot experience from 2007 to 2017 over 217 patients but with a 35% participation rate at 4 years [35], with other studies including only 74 patients with a 3-month follow-up [32], 70 patients at 6 months [28], 42 patients for 12 months [31], 27 patients for 20 months [30], or 73 patients for 24 months [36]. Thus, the strengths of the presented study are the description of the largest case series reported in France, one of the largest numbers of cases worldwide published and a high and sat- What can patients expect in the long term from radiofrequency thermocoagulation of hemorrhoids on bleeding, prolapse, quality of life, and recurrence: "no pain, no gain" or "no pain but a gain"?…”
Section: Discussionmentioning
confidence: 99%
“…Die Radiofrequenzablation (RFA) mittels einer Sonde und die Laserhämorrhoidoplastie (LHP) wirken durch die Einwirkung von Hitze innerhalb des Hämorrhoidalgewebes. Die Sonden werden entweder an der Linea anocutanea subanodermal/submukös vorgeschoben und dann sukzessive während der Hitzeentwicklung zurückgezogen oder direkt in die vergrößerten Hämorrhoidalknoten eingeführt [17]. Obwohl es Beschreibungen kleinerer Patientenkollektive gibt, die mittels Sonden-RFA angeblich auch bei fortgeschrittenem Hämorrhoidalleiden suffizient therapiert wurden [18], eignet sich die Technik aus Sicht der Autoren nicht zur Behandlung von Hämorrhoiden Grad III und IV.…”
Section: Andere Methodenunclassified
“…The energy is converted into heat to destroy haemorrhoidal vessels and initiate a process of submucosal fibrosis. Although radiofrequency ablation (RFA) by the Rafaelo © procedure is already used in many European countries, there are only few studies on this minimally invasive technique [9][10][11][12][13][14]. Most of them are retrospective with low numbers of patients and conducted in one or two centres.…”
Section: Introductionmentioning
confidence: 99%
“…At 3 months, the rate of patients reporting bleeding (21% vs. 84%, p < 0.001), prolapse (34% vs. 91.3%, p < 0.001) and anal discomfort (0/10 vs. 5/10, p < 0.0001) decreased significantly. Median medical leave was 4 days [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Postoperative pain was 4/10, 1/10, 0/10 and 0/10 at weeks 1, 2, 3 and 4.…”
mentioning
confidence: 99%